2005
DOI: 10.1590/s1020-49892005000100002
|View full text |Cite
|
Sign up to set email alerts
|

La enfermedad diarreica aguda: un reto para la salud pública en Colombia

Abstract: The ineffectiveness of health promotion and disease prevention activities in a population with easy access to health services set the stage for the appearance of cases of diarrhea with dehydration. Rotavirus infection plays an important role in the severity of ADD among Colombian children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 20 publications
1
4
1
7
Order By: Relevance
“…Differences among socioeconomic groups are an important factor in the genesis of diseases related to the widespread microbiological contamination of the environment [32]. Several studies in Latin America have shown that adequate hygiene practices and good sanitary conditions decrease the levels of contamination significantly [14, 15, 33]. In our study, due to the sample size, no significant differences among strata were shown in the STEC contamination level of ground beef.…”
Section: Discussioncontrasting
confidence: 49%
“…Differences among socioeconomic groups are an important factor in the genesis of diseases related to the widespread microbiological contamination of the environment [32]. Several studies in Latin America have shown that adequate hygiene practices and good sanitary conditions decrease the levels of contamination significantly [14, 15, 33]. In our study, due to the sample size, no significant differences among strata were shown in the STEC contamination level of ground beef.…”
Section: Discussioncontrasting
confidence: 49%
“…Genetic variability is, thus, increased and, conse quently, nontypeable strains appear ( 12,29,51). Fischer et al ( 19) found that in 20% of nontypeable P strains, the VP4 gene showed point mutations in the P [8] primer when it was amplified and sequenced. Iturriza-Gomara et al (34) found that the recognition site for the P [8] primers shows variability and, therefore, the previously designed primers (22) do not amplify these genes.…”
Section: Discussionmentioning
confidence: 99%
“…Fischer et al ( 19) found that in 20% of nontypeable P strains, the VP4 gene showed point mutations in the P [8] primer when it was amplified and sequenced. Iturriza-Gomara et al (34) found that the recognition site for the P [8] primers shows variability and, therefore, the previously designed primers (22) do not amplify these genes. Consequently, we suggest that nontypeable strains must be sequenced to achieve their identification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This city has a population of about 525,000 and is located on a plateau of the Andes at 959 meters above sea level, with an average temperature of 23°C and annual rainfall of 1041 mm. The city has over 90% coverage for basic utilities including those for water, electricity, telephone, gas, and garbage collection with a frequency of three times a week [13]. The coverage of pediatric hospital beds in this region is 0.48 per 1000 population for children under 12 years of age.…”
Section: Methodsmentioning
confidence: 99%